The measurement properties of the five‐item International Index of Erectile Function (IIEF‐5): a Dutch validation study. (9th October 2015) - Utomo, E.; Blok, B. F.; Pastoor, H.; Bangma, C. H.; Korfage, I. J.
Summary: Erectile dysfunction (ED), affecting men worldwide, is associated with worse mental health. The severity of ED as well as the effect of its treatment can be assessed using valid self‐reported outcome measures. A widely used measure is the International Index of Erectile Function short form (IIEF‐5) which is not yet validated in Dutch. The objective of this study was to translate the IIEF‐5 into Dutch and to investigate its reliability and validity to provide a useful evaluation tool. The IIEF‐5 was translated into Dutch following standardized forward–backward procedures. To conduct this observational study, men with symptoms of ED completed the Dutch IIEF‐5 at inclusion, 1 week later, and 6 months after inclusion. A population‐based sample (reference group) completed the IIEF‐5 once. The quality domains reliability and validity were addressed by testing the measurement properties internal consistency, reliability, measurement error, and content validity. Data of 82 patients and 253 reference group participants were analyzed. Internal consistency was adequate with Cronbach's alpha of 0.94 in both patient and reference group. In patients, the test–retest reliability was adequate with an intra‐class correlation coefficient for agreement of 0.88. A floor effect was present in the patient group (42%), though not in the reference group (3%). There was no ceiling effect in patients (0%), while this was present in the reference group (17%). Analysis of responsiveness was not possible due to the limited number of patients receiving treatment. The Dutch IIEF‐5 is a reliable and valid measure to determine severity of symptoms of ED. This evaluation tool is valuable for clinical use and interpreting results across international clinical studies. The context of a patient's sexual life is, however, indispensable and should be taken into account.